2010
DOI: 10.1002/humu.21230
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis ofPMS2: mutation detection and avoidance of pseudogenes

Abstract: Germline mutation detection in PMS2, one of four mismatch repair genes associated with Lynch syndrome, is greatly complicated by the presence of numerous pseudogenes. We used a modification of a long-range PCR method to evaluate PMS2 in 145 clinical samples. This modification avoids potential interference from the pseudogene PMS2CL by utilizing a long-range product spanning exons 11-15, with the forward primer anchored in exon 10, an exon not shared by PMS2CL. Large deletions were identified by MLPA. Pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 25 publications
2
83
1
1
Order By: Relevance
“…Detection of pathogenic mutations using current methodologies is likely incomplete given the number of patient samples with isolated loss of PMS2 protein expression for which pathogenic mutations are not identified [Senter et al, 2008;Vaughn et al, 2010]. In those samples in which pathogenic mutations are detected, two studies showed that large deletions of one or more exons comprised 21% and 37% of PMS2 mutations [Senter et al, 2008;Vaughn et al, 2010].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Detection of pathogenic mutations using current methodologies is likely incomplete given the number of patient samples with isolated loss of PMS2 protein expression for which pathogenic mutations are not identified [Senter et al, 2008;Vaughn et al, 2010]. In those samples in which pathogenic mutations are detected, two studies showed that large deletions of one or more exons comprised 21% and 37% of PMS2 mutations [Senter et al, 2008;Vaughn et al, 2010].…”
Section: Introductionmentioning
confidence: 96%
“…For sequencing, long-range amplification can be utilized to circumvent coamplification of pseudogenes [Clendenning et al, 2006;Vaughn et al, 2010]. For deletion/ duplication analysis by MLPA, it is necessary to locate probes over sequence unique to the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this point, our study suggests that PMS2, which does not contribute greatly to Lynch Syndrome [41], could be considered a good candidate for evaluation. Moreover, as the commonly known technical difficulties of analyzing PMS2 are slowly being overcome by new analysis strategies [41][42], critically needed evidence concerning the role of PMS2 can be expected. For instance, recently, ten Broeke et al reported a standardized incidence ratio of 3.8 for breast carcinomas, which led them to suggest adding mammography from age 40 years in PMS2 families with evident clusters of BC [43].…”
Section: Discussionmentioning
confidence: 99%
“…The probe design of the TruSight Cancer Content suggests that the assay does not discriminate PMS2 from its 15 pseudogenes (36 ), and this would affect results interpretation. Previous studies have attempted to enrich for PMS2 using careful probe design (25,37,38 ); however, the high sequence homology has made absolute enrichment elusive. This emphasizes the need for careful probe design for accurate diagnosis, whether by NGS, Sanger sequencing, or alternative methods.…”
Section: Discussionmentioning
confidence: 99%